A distinctive HPHT platform with different types of large-volume press subsystems at SECUF - Yufei Ge; Shuailing Ma; Cun You; Kuo Hu; Chuang Liu; Yixuan Wang; Xinglin Wang; Xinyang Li; Hongyu Li; Qiang Tao; Shuqing Jiang; Lu Wang; et al. (Matter and Radiation at Extremes, 2024)
Large-volume presses (LVPs) providing large volumes, liquid media, deformation capability, jump compression, and in situ measurements are in great demand for high-pressure research, particularly in the fields of geoscience, condensed matter physics, material science, chemistry, and biology. A high-pressure and high-temperature (HPHT) platform with different LVP subsystems, both solid-state and liquid environments, and nonequilibrium subsystems, has been constructed at the Synergetic Extreme Condition User Facility, Jilin University. This article describes the construction of the different subsystems and provides an overview of the capabilities and characteristics of the different HPHT subsystems. A large sample volume (1000 mm3) at 20 GPa is achieved through the use of a belt-type apparatus in the solid-state subsystem. HPHT conditions (1.8 GPa and 1000 K) are realized in the liquid subsystem through the use of a piston–cylinder-type LVP with optical diamond windows for in situ spectroscopic measurements. A maximum pressure jump to 10.2 GPa can be reached within 20 ms in the nonequilibrium subsystem with the use of an improved bladder-pressurization jump press. Some typical results obtained with different LVPs are briefly reviewed to illustrate the applications and advantages of these presses. In summary, the platform described here has the potential to contribute greatly to high-pressure research and to innovations in high-pressure technology.